Evaluation of adherence, distress and quality of life for type 2 diabetes melitus patients In Puskesmas Wedarijaksa I and Puskesmas Trangkil Kabupaten Pati - Perwitasari, Dyah Aryani; Urbayatun, Siti; Wilisa, Oni Yulianta (Pharmaciana, 2018)
Diabetes mellitus is chronic disease that needs the complex and a long term medical treatment. Patient adherence and level of distress can affect patient quality of life. The purposes of this study is to examine patients adherence, distress, and quality of life patients type 2 diabetes mellitus in Kabupaten Pati. This study used cross sectional design and data patients collection techniques were conducted prospective data. The subjects of research were patients with Type 2 diabetes amounted to 126 people. Instruments used in this research is Medication Adherence Respon Scale (MARS) questionnaire to measure patients adherence, Diabetes Distress Scale (DDS) to measure distress, and EQ-5D-5L questionnaire to measure quality of life. Data analysis statistic used Mann Whiney test, and linier regression. This study was dominated by female patients 78.6%. The mean age of DMT2 patients was 54.49 ± 6.19 years. The average value of adherence (MARS) was 21.33 ± 2.90 including in moderate adherence. The mean total of DDS score was 1,56±0,42 including not distress level and the highest is the emotional burden domain. The mean value of EQ5D5L index was 0.729 ± 0.161. The results showed a significant association (p <0.05) between patient characteristics age and duration of sick with adherence. There were significant association (p <0.05) between age to physician distress, gender with emotional, marital status with emotional and interpersonal distress, duration of sick to physician distress and management therapy distress. Marital status and income had significant relationship to quality of life. Emotional burden domain had significant relationship to quality of life. Multivariate analysis showed that the relationship of adherence and distress by the emotional burden to quality of life. This study concluded the significant relationship between adherence, distress and quality of life.